Entrepreneurial competence, financial literacy, and sustainable performance: exploring the moderating role of resilience in entrepreneurship (in MSMEs in Yogyakarta) - Prastyatini, Sri Lestari Yuli; Irawan, Mairizon (Proceeding International Conference on Accounting and Finance, 2026)
Study This aim For test influence competence entrepreneurship and literacy finance to performance sustainable MSMEs, as well as analyze role resilience entrepreneurship as variables moderation in connection said. Research This expected give benefit practical for MSME actors and manufacturers policy in develop improvement strategies ability and resilience business For support sustainability business. In general theoretical, research This expand study literature about factors that influence performance sustainable MSMEs with notice aspect competence, literacy finance, and resilience entrepreneurship as variables. The research sample was taken using a purposive sampling technique, so that respondents were relevant to the research criteria. Data were collected through questionnaires distributed to 113 MSMEs. The results of this study indicate that entrepreneurial competence and financial literacy variables have a positive and significant effect on sustainable performance. These two variables play an important role in improving the ability of business actors to manage their businesses effectively in facing market challenges. While entrepreneurial resilience is able to significantly moderate the relationship between financial literacy and sustainable performance, entrepreneurial resilience is not able to significantly moderate the relationship between entrepreneurial competence and sustainable performance. The results of this study can help MSMEs in developing more effective MSMEs. This study has a novelty by simultaneously testing the effect of entrepreneurial competence and financial literacy on sustainable performance, and including entrepreneurial resilience as a dual moderating variable in both relationships. This model has not been widely analyzed in previous studies, especially in the context of Indonesian MSMEs. In addition, the study applies the Resource-Based View (RBV) approach to position entrepreneurial competence, financial literacy, and resilience as internal capabilities that determine sustainable competitive advantage. The latest empirical data from 2025 on MSMEs in Yogyakarta provides additional contributions that strengthen the novelty of this research.